STUDI JENIS VEGETASI PAKAN BEKANTAN (Nasalis larvatus, Wurmb) DI KAWASAN TAMAN NASIONAL DANAU SENTARUM KAPUAS HULU KALIMANTAN BARAT - Ananda, Restu; Erianto, .; Prayogo, Hari (Universitas Tanjungpura, 2019)
Proboscis Monkey is a kind of primate which is found in Indonesia, especially in Borneo Island (endemic) it is protected from colonialsm. They can be survived in the abundant natural resources. This research uses track combination methode with plotted area in purposive sampling on the bekantan found. Base on the result of the research is found 20 kinds of plants from 14 families 8 kinds of them is plants that eaten: Kawi (Shorea balangeran), Kebesi (Memecylon edule), Putat (Barringtonia acutangula), Sikup (Garcinia celebica), Temirit (Timonius flavescens) Kayu Tahun (Carallia sp), Mentangis (Ixora mentangis) dan Rengas (Gluta renghas), it is obtain that shoots, leaves is most likely eaten by it from the result of data analysis poles (HÌ… = 0,82) is found the highest plant diversity index, it is followed sapling (HÌ… = 0,77), trees (HÌ… = 0,67), seeding (HÌ… = 0.61). From the repapitulation of abundance plants of species is uneven.Keyword : Bekantan, Feed source of bekantan and Vegetation.